Effects of rutin and quercetin on monooxygenase activities in experimental influenza virus infection - Savov, V.M.; Galabov, A.S.; Tantcheva, L.P.; Mileva, M.M.; Pavlova, E.L.; Stoeva, E.S.; Braykova, A.A.
The aim of this work is to study the effect of the flavonoids rutin and quercetin on hepatic monooxygenase activities in experimental influenza virus infection (EIVI). EIVI causes oxidative stress in the whole organism. This is confirmed by the rapidly increased concentrations of thiobarbituric reactive substances in influenza-infected mice: lungs - 290
Keywords: INFLUENZA; MONOOXYGENASE ACTIVITY; OXIDATIVE STRESS; RUTIN; QUERCETIN